OSOGBO FESTIVAL OF IMAGES AND YORUBA ART HISTORY (1994)
Osogbo, the capital of Osun State of Nigeria, has become very popular as a centre of art and culture in Yorubaland for many years. Both traditional and contemporary art forms are kept alive in the town, but the attention of the outside world has been focused mainly on the latter while the major aspect of the former, the festival of images, has been conspicuously neglected. The main purpose of this study is to examine this annual ceremony which involves a processional display of the traditional (sculptural) images of the town for a deeper understanding of the artistic heritage of the town and the entire Yorubaland. Through participant observation and interview, the origin, development and sociological significance of the festival were investigated. The images involved, in the festival were identified and compared with the representation and worship of the deities in other Yoruba towns such as Ilobu, Ibadan and Esie. It was found that the annual festival of images at Osogbo is meant to honour, propitiate and petition Sonponna) the Yoruba god of small-pox and other pestilences; and that Yoruba festivals involving many images are mostly festivals of river deities at which the symbolic images of the respective deities, priests, priestesses or worshippers play a very prominent role. The festivals also seem to have some historical implication. They are in one way or the other connected with Old Oyo. The inhabitants of the present site of Esie migrated to the town from Old Oyo in the eighteenth century. Available evidence shows the images at Esie as the oldest, dated to the eleventh century A.D. However, there is no proof that the festival has existed uninterrupted since that time. The most recent instances are therefore not ascertained as continuations of the practices in Esie. They are probably instances of revivalism.